PENGARUH VIDEO EXPLAINER TERHADAP MOTIVASI BELAJAR PESERTA DIDIK KELAS IV SDN 1 REJOSARI PADA MATERI IPA - Sari, Indah Permata; Pertiwi, Ratih Purnama; Sinensis, Arini Rosa (JISPE Journal of Islamic Primary Education, 2024)
This research aims to determine the effect of explainer videos on the learning motivation of class IV students at SDN 1 Rejosari on science material. This writing is motivated by the low learning motivation of students in studying science material on animal body parts and their functions in elementary schools. This research uses a quantitative experimental method with a Quasi Experimental Design research type. The sample in this research was class IV students at SDN 1 Rejosari, totaling 34 students. Data collection techniques use observation, documentation and questionnaires. The data analysis technique uses average learning motivation, normality test, homogeneity test and independent sample t test. Based on the analysis that has been carried out, the results show a significance value of 0.000 < 0.05 for variables animal body parts and their functions.